2010
DOI: 10.1007/s10766-010-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Mixed-Mode OpenMP/MPI Implementations

Abstract: With the current prevalence of multi-core processors in HPC architectures, mixed-mode programming, using both MPI and OpenMP in the same application, is seen as an important technique for achieving high levels of scalability. As there are few standard benchmarks written in this paradigm, it is difficult to assess the likely performance of such programs. To help address this, we examine the performance of mixed-mode OpenMP/MPI on a number of popular HPC architectures, using a synthetic benchmark suite and two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Graph coloring color growth bounded graphs such as unit disk graphs; for resolving resource conflicts. Our study of existing benchmark suites [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18] has found that none of them meet majority of the aforementioned key requirements. Our goal is to design a benchmark suite that meets all our stated requirements.…”
Section: Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Graph coloring color growth bounded graphs such as unit disk graphs; for resolving resource conflicts. Our study of existing benchmark suites [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18] has found that none of them meet majority of the aforementioned key requirements. Our goal is to design a benchmark suite that meets all our stated requirements.…”
Section: Problemmentioning
confidence: 99%
“…While PARSEC, JGF, NPB and BenchERL also contain a few kernels, benchmark suites like PBBS [4] focus only on kernel benchmarks. Similarly, JGF contains a few micro-kernels as well, while EPCC [11,8] and IntelMPI [14] contain only micro kernels. Compared to the application-oriented benchmarks, the kernel benchmarks are small in size, simpler to understand, easier to debug and provide insights on how a certain algorithm behaves.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is associated to GCC but simple to deploy in existing environments as it does not modify the compilation chain. To show the impact of PARCOACH analysis on the compilation and execution time, we tested the NAS-MZ [12], AMG benchmark [1], the EPCC suite [2] and HERA [5]. All results were conducted on Tera100, a petaflopic supercomputer at the CEA.…”
Section: Resultsmentioning
confidence: 99%
“…The usage of parallelism improves the execution time and allows the treatment of more voluminous databases. We envisage to experiment P-STM on machines more larges (with more cores) and to develop hybrid distributed version with the library MPI (Message Passing Interface) [13]. Another perspective is to test another way to proceed for generating candidates: to generate only signature candidates (without generating candidate itemsets).…”
Section: Discussionmentioning
confidence: 99%